2019
DOI: 10.1055/s-0039-3400483
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Feasibility of the Self-Administered ISTH-Bleeding Assessment Tool

Abstract: Introduction  Standardized bleeding assessment tools (BATs), such as the International Society for Thrombosis and Hemostasis (ISTH)-BAT, are screening instruments used during the diagnostic workup of suspected bleeding disorders. A self-administered ISTH-BAT (self-BAT) would enhance screening and save time during an outpatient clinic visit. Aim  This study was aimed to investigate the reliability and feasibility of the self-BAT. Methods  The electronic self-BAT was created from the ISTH-BAT and paper-version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 10 publications
(16 reference statements)
6
17
1
1
Order By: Relevance
“…Another explanation could be that the tools are not identical, and therefore, differences in question and scoring can lead to discrepancies. Nevertheless, a 3% misclassification is comparable to previous findings, 14 and we expect that the expert‐ISTH‐BAT can also be erroneous in few cases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another explanation could be that the tools are not identical, and therefore, differences in question and scoring can lead to discrepancies. Nevertheless, a 3% misclassification is comparable to previous findings, 14 and we expect that the expert‐ISTH‐BAT can also be erroneous in few cases.…”
Section: Discussionsupporting
confidence: 89%
“…However, the ISTH‐BAT is expert‐administered (expert‐ISTH‐BAT) and should be filled out by healthcare practitioners with knowledge of bleeding disorders, which limits its use as a general screening tool. A patient‐administered version of the expert‐ISTH‐BAT (self‐ISTH‐BAT) is developed 12 and has been validated on individuals suffering from VWD, 12 hemophilia, 13 and congenital platelet defect (CPD) 14 along with the general population 15 . The self‐ISTH‐BAT is in English and therefore not applicable in non–English‐speaking countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of tools in the clinical setting was thought to be cumbersome and time‐consuming prompting development of a tool designed for self‐administration. The self‐administered BAT has been deemed reliable and feasible to evaluate for an underlying bleeding disorder 27 . Overall, the BAT tools show better sensitivity than specificity and higher negative predictive value 28 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study also showed that it was discriminatory in haemophilia as well 23 . In fact, the self‐assessed BAT has also been shown to be as effective in screening for abnormal bleeding as the healthcare professional administered BAT 24 . So it is possible to imagine a situation where a validated self‐assessed BAT is given to all school children for their parents to provide the responses.…”
Section: Alternative Approaches ‐ What Is Ideal and What Is Possible?mentioning
confidence: 99%